THE NOTARY'S CRIMINAL LIABILITY FOR DEEDS USED IN MONEY LAUNDERING CRIMES IS ASSOCIATED WITH THE DOCTRINE OF DEELNEMING - Medica Rizkasyah Taufiq; Imas Rosidawati Wiradirja (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
ABSTRACT Deeds made before a Notary against certain legal acts may be parties who are perpetrators of money laundering crimes who utilize the services of a Notary, this action is carried out by the perpetrator so that the money laundering transaction avoids legal entanglements due to the confidentiality of the position owned by the Notary. Notaries may be caught up in acts of inclusion in criminal acts, especially in corruption crimes that have characteristics in terms of subjects, objects and deeds and are carried out by people who have special skills or have the authority, opportunity or means that exist in them because of their position or position. The method used in this study is empirical juridical, which is research that seeks to connect the prevailing legal norms with the reality that exists in society. The research specifications used are descriptive analytical which is expected to be able to provide a detailed, systematic, and comprehensive picture of all related matters. The results showed that a new Notary can be held accountable if he has made a mistake or committed an act that violates laws and regulations. The imposition of criminal sanctions against notaries can be carried out as long as the restrictions as mentioned above are violated. Aspects of legal protection for Notaries related to the relationship between criminal law institutions are in connection with the right to deny Notaries that must be carried out and the presence of the Honorary Notary Assembly is an effort made by the government in providing a form of legal protection for notaries in carrying out their duties as general officials.